SCALP LACERATION: A POPULATION BASED ANALYSIS AMONG THE URHOBOS IN DELTA STATE, NIGERIA - Ese, Anibor; Osaretin, Mabiaku Yvonne; Brenmound, Jones-Dibie; Richard, Igoh (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
Following a traumatic event, head damage is the main cause of mortality and morbidity. This inquiry established the preponderance of Scalp Laceration among the Urhobo population in Delta State, Nigeria. The study adopted a cross sectional study scheme. The study sample comprised of male and female individuals who are from the Urhobo ethnic group. This scrutiny was carried out in Abraka, Eku and Warri in Delta State, Nigeria. The sample size for this study is 384 and the cluster sampling technique was used to select the sample for the study. The required data was collected with the aid of a well-structured self-administered questionnaire. The results were analysed by means of Statistical Package for the Social Sciences (SPSS), version 25.0. Results were presented in frequency distributions, pie charts and cross-tabulation. Chi-square gaged significant differences at a confidence level of 95% while p < or = 0.05 was considered as statistically significant. The occipital region of the scalp was shown to be the most recurrent site of scalp laceration.